2007
DOI: 10.1002/rmv.553
|View full text |Cite
|
Sign up to set email alerts
|

RNA interference and HIV‐1 infection

Abstract: Life-prolonging antiretroviral therapy remarkably reduces viral load, but it does not eradicate the virus. An important obstacle preventing virus clearance is the presence of latent virion reservoirs in the host. However, new promising antiviral approaches are emerging, and a number of host cell factors involved in the disease progression and control of HIV-1 replication have been recently discovered. For instance, the RNA interference (RNAi) mechanism, besides many functions conserved throughout evolution, wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 148 publications
0
10
0
Order By: Relevance
“…[23][24][25][26][27][28][29] Recent studies have demonstrated that RNAi can be exploited in order to target genetic sequences of a variety of human and animal viruses including HIV-1, Poliovirus, Human Papillomavirus (HPV), Hepatitis C Virus (HCV), Hepatitis B Virus (HBV), Influenza Virus, Severe Acute Respiratory Syndrome Coronavirus (SARS-CoV), and Feline Immunodeficiency Virus (FIV). 9,[30][31][32][33][34][35][36][37][38][39] These studies confirmed that RNAi technology represents a promising gene therapeutic approach to control viral infection and disease progression. Previous studies applying RNAi directed to structural genes inhibited viral replication of HIV and FIV.…”
Section: Introductionmentioning
confidence: 54%
See 3 more Smart Citations
“…[23][24][25][26][27][28][29] Recent studies have demonstrated that RNAi can be exploited in order to target genetic sequences of a variety of human and animal viruses including HIV-1, Poliovirus, Human Papillomavirus (HPV), Hepatitis C Virus (HCV), Hepatitis B Virus (HBV), Influenza Virus, Severe Acute Respiratory Syndrome Coronavirus (SARS-CoV), and Feline Immunodeficiency Virus (FIV). 9,[30][31][32][33][34][35][36][37][38][39] These studies confirmed that RNAi technology represents a promising gene therapeutic approach to control viral infection and disease progression. Previous studies applying RNAi directed to structural genes inhibited viral replication of HIV and FIV.…”
Section: Introductionmentioning
confidence: 54%
“…The inhibition of HIV-1 and FIV [29][30][31][32][33]40,45,46 replication among other viruses could be accomplished by the shRNA expression in established and primary cell lines. Here, we investigated the feasibility of using RNAi technology, based in shRNA expression, aiming at controlling FeLV infection in feline cell lines.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Accordingly, several large DNA mammalian viruses have been shown to encode their own miRNAs. RNAi is directly implicated in HIV replication [33]. Dicer mutant mice are hypersusceptible to infection by the RNA virus vesicular stomatitis virus [57].…”
Section: Mirna Regulation Of Infectionmentioning
confidence: 99%